A dinâmica da paisagem no estado do Amapá: análise socioambiental para o eixo de influência das rodovias BR-156 e BR-210 - Rauber, Alexandre Luiz (2019)
This thesis is dedicated to study the dynamics of the landscape in Amapá state. More specifically, on the area comprised in a polygon band of 50 km on the axis of influence of BR-156 and BR-210 Highways. This polygonal covers 3,81 millions hectares and it was defined in the research based on criteria and spacial patterns that evidence anthropic activities. The main objective of this thesis is to analyze the dynamics of the landscape as a performance scenario and articulation of diferent intervening actors involved in the expansion of the economic frontier in the axis of influence of the BR-156 and BR-210 Highways from Amapá state. The specific objectives are to characterize the landscape based on geographic and socioeconomic aspects; to distinguish the role and performance of the actors involved in dynamics of Amapá landscape, to understand the transformation of the landscape from the spacial patterns of occupation and the physical environmental aspects involved in Amapá Forest area and Cerrado in the axis of influence as well to introduce the trends and perspectives of the spacial configuration in the studied area. Considering the fronts of occupation dinamize the landscape of Amapá state and they cross the axis of BR-156 and BR-210 Highways from south to north and from east to west, the thesis presents three hypotheses: 1) the expansion of agricultural and environmental frontier occurs, concomitantly, on Forest and Cerrado áreas of Amapá; 2) the rural settlements constitue and represent the greatest anthropic pressure on the Forest landscape and 3) the polygon’s area influence analyzed tends to be completely incorporated by the intervening actors captained by the new fronts of soyculture and logging. From the theoretical and methodological point of view, it was used the landscape as a category of Geography, important and fundamental for the environmental and spacial analysis, since it allows to understand the different processes of transformation arising from the articulation betweensociety and nature. The methodological procedures were developed from the production and crossing of quantitative and qualitative data generated by techniques of Remote Sensing and Geoprocessing, using secondary data collected with the various government agencies and technical reports and management plans. This research produced several multitemporal mappings trough satellite and radar images to analize the patterns and the space dynamics in the influence axis of BR-156 and BR-210 highways, from 1991th to 2015th years, and they evidence the acting and the perspectives of new economical fronts – wood and soyculture – in the changing and dinamic of landscape units along the polygon. The fronts of exploration and the fronts of expansion act in parallel and at the same time, however, the greater intensity of the antropic activity and of conversion of area happens in the unit of Cerrado landscape. About 2.2% of the total area of the Forest landscape unit has been converted into a shallow cut for agriculture, mainly in Rural Settlements, Indigenous Lands and Livestock Projects, intervening actors that have been losing prominence in recent years to the increasing forest degradation caused by logging. Sojiculture appears recently in the state scene, associated with forestry already installed since the 1980th, as protagonist in the transformation of the landscape of 12% of the Cerrado.